2013
DOI: 10.1039/c3ra23208e
|View full text |Cite
|
Sign up to set email alerts
|

Natural or synthetic nucleic acids encapsulated in a closed cavity of amphiphiles

Abstract: In this review some aspects of the interactions of organized structures of amphiphiles with natural or synthetic DNAs are briefly considered. In particular DNAs encapsulated in closed cavities of amphiphiles, specifically giant vesicles and water-in-oil droplets and reverse micelles, are dealt with. Two main applications of giant vesicles are reviewed in detail, namely their use as microreactors where reactions can be followed by optical microscopy on a single vesicle and in synthetic biology as protocell mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 257 publications
(290 reference statements)
0
1
0
Order By: Relevance
“…The influence of spatial confinement on polyelectrolytes has been extensively investigated. The equilibrium conformation of a highly charged polymer chain confined in a cavity is evidently governed by the interplay between energetic and entropic factors coming from the confinement shape and size relative to the chain length, the chain bending stiffness, the electrostatic interaction between the charged monomers, counterions, and the solvent, as well as their configurational entropy. For short flexible polyelectrolytes confined in a neutral spherical cavity, Kumar and Muthukumar using self-consistent field theory demonstrated that, for a given radius of the spherical cavity and fixed charge density along the backbone of the chain, solvent and small ion entropies dominate over all other contributions to the free energy.…”
mentioning
confidence: 99%
“…The influence of spatial confinement on polyelectrolytes has been extensively investigated. The equilibrium conformation of a highly charged polymer chain confined in a cavity is evidently governed by the interplay between energetic and entropic factors coming from the confinement shape and size relative to the chain length, the chain bending stiffness, the electrostatic interaction between the charged monomers, counterions, and the solvent, as well as their configurational entropy. For short flexible polyelectrolytes confined in a neutral spherical cavity, Kumar and Muthukumar using self-consistent field theory demonstrated that, for a given radius of the spherical cavity and fixed charge density along the backbone of the chain, solvent and small ion entropies dominate over all other contributions to the free energy.…”
mentioning
confidence: 99%